Research advances on the effects of serum-dominated and glomerular deposited IgG subclasses and complement molecules on glomerular diseases - Qi Li; Yue Wang (Editorial Department of Journal of Clinical Nephrology, 2024)
IgG subclasses and complement molecules of sera-dominant and depositing in glomeruli play major roles in development and prognosis in patients of glomerular diseases. In patients of lupus nephritis (LN) due to systemic lupus erythematosus (SLE), IgG subclasses depositing in sera and glomeruli are predominantly IgG1 and IgG3. And C1q and C3 deposits in glomeruli may be observed. Complement activation is predominant in classical pathway with an acute onset. A more severe state denotes a worse prognosis. A lower serum level of C3/C4 reflect disease activities. In patients of primary membranous nephropathy (PMN), IgG4 is a predominant IgG subclass deposited in sera and glomeruli. Deposition of complement C3/C4d is common in glomeruli. And complement activation is dominated by lactin pathway with a slower onset, a milder status and a better prognosis and an elevation of specific anti-PLA2R antibodies in sera reflects disease activity. In IgA nephropathy and ANCA-associated vasculitis kidney injury, IgG subclasses and complement molecules in sera and glomerulus have been reported. Whereas infectious, metabolic and tumor-associated glomerular diseases are less thoroughly studied, the values of diagnosis, differential diagnosis and prognostic assessment should be further explored.